The Call of Duty and Adverse Circumstances - Cosimo Jaś Williams; Jan Kłos (Language, Culture, Politics)
This paper is a commentary on the short story entitled The Healer, and delves into the philosophies that precede and seek to explain the actions of the characters and the relevant plot points. Centring around the bond between human beings and the situations that life has brought to them, this commentary sets out to seek out why humans react the way they do in the face of pain and suffering. With the aid of Jaspers’ philosophy, and the works of Graham Greene, C. J. Williams and J. Kłos proceed to expand upon what humans truly desire most when driven to times of desperation, and what guides them to make potential life altering decisions. When dealing with the world of The Healer, the chaotic mix of a setting based in World War Two, the presence of disease, and the need to uphold loyalties and duties provides a formula ripe for exploring the relationship between suffering, family, and adversities.